Efeito da massoterapia e da utilização de placa oclusal sobre a atividade muscular e sobre a força de mordida em crianças com bruxismo. - Bortoletto, Carolina Carvalho (2012)
Bruxism can be defined as parafunctional habit of grinding or clenching the teeth, which can occur during sleep or wakefulness. The aim of this study was to evaluate the bite force and muscular activity variation after performing massage therapy and use of occlusal splint in children with bruxism. We selected 48 children, divided into 4 groups: Group 1 monitoring without bruxism; Group 2 massage therapy; Group 3 occlusal splint; Group 4 monitoring children with bruxism. All children were submitted to initial and final evaluation of bite force and muscular activity. Children in group 2 were submitted to 15 sessions of facial massage therapy with duration of 30 minutes each, and group 3 was treated with occlusal splint for a period of 30 days. The results were computed and statistical analysis performed using a significance level of 95% (p ≤ 0.05). There was a statistically significant difference in muscle activity of individuals in group 3 (p = 0.003) and the bite force of group 2 (p = 0.001) and 3 (p = 0.007), which allowed us to conclude that the use of occlusal splints caused a decline in muscle activity and an increase in bite force of bruxism children, and that massage therapy did not alter the muscle activity, but provided an increase in bite force of these children.